(untitled) (Altre Modernità, 2012)
Since 1995, tourism leads the economical base of Costa Rica. The ecological tourism has been the most developed since the biodiversity is internationally accepted; whereas the cultural tourism is embryonic as well as combined with other alternatives. In this paper, we are going to analyze the lexicon used in three texts on discursive genre “guide book” taken from the Communal and Rural Handbook of Tourism and an advertising brochure. We compare the lexicon of an official text with two others from the communal-rural tourism, in relation to cultural and environmental tourism from different places of the country. With the fundamental presumption that tourism as economical enterprise or cultural industry uses publicity with the purpose of capturing the diverse kinds of population and selling their offer; we take the theoretical referents of the language of tourism and some other elements of the critical analysis of discourse. It is important to mention that for a long time, the cultural diversity was left out, and the touristic development of the country covered up the physical presence or the cultural legacy of some components of the national population. Nevertheless, with the development of the touristic activity it is used the image of pluralism in the regional plans for the development of the region. In the every day offer are included hiking on paths and some other cultural traditions. Utterances are reaffirmed in the lexicon plan, which allude to touristic repertoire of principal ideas as well as enhances the authenticity of the offer.